Formation of Imidazolidine-benzothiazole–Copper(II) Complexes via a Copper-Mediated Room-Temperature C–H Activation of Imidazolidinecarbothioamides - Sahoo, Santosh K.; Jena, Himanshu Sekhar; Majji, Ganesh; Patel, Bhisma K. (Synthesis, 2014)
Treatment of N-aryl-2-(arylimino)imidazolidine-1-carbothioamide, and unsymmetrical thiourea, with copper(II) chloride or bromide results in aryl sp2 C–H activation (C–S bond formation) at room temperature to form a 2-[2-(arylimino)imidazolidin-1-yl]benzothiazole with concurrent formation of a 2-imidazolidin-1-ylbenzothiazole–copper(II) complex. In all the complexes the imine and benzothiazole nitrogens are s-cis, whereas in the isolated ligands they are s-trans oriented. Due to the presence of a suitable H-donor site and halogen atoms in the metal complexes and ligands, several supramolecular assemblies exist through H-bonding interactions; classical N–H···X–Cu (F, Cl, Br), nonclassical C–H···X–Cu H–bonds, and halogen···π and halogen···halogen interactions.
Keywords: copper catalysis; imidazolidinecarbothioamide; C–H activation; aminothiazole; halogen bonding; supramolecular assembly